612. Increase in Perinatal HIV Infection in North Florida: Missed Opportunities to Prevent Maternal-to-Child Transmission in Rural Areas. (26th November 2018) - Ryan, Kathleen; Campbell, Vicky; Washam, Matthew; Lew, Judy; Lawrence, Robert
Abstract: Background: The rate of mother-to-child transmission of human immunodeficiency virus (HIV) in the United States has significantly declined due to routine opt-out HIV testing of pregnant women and implementation of effective prenatal, intrapartum and postnatal interventions. This includes first trimester HIV testing and retesting in the third trimester in areas with high HIV prevalence or in high-risk social situations. The University of Florida Pediatric Infectious Disease division serves a 31 county area for pediatric HIV care that includes Gainesville, Tallahassee and the entire Florida panhandle encompassing mostly rural counties. There are two HIV perinatal coordinators for pregnant women serving 19 of the counties. Methods: HIV-positive mother–infant pair chart review 2008–2018. Results: Between 2008 and 2012 there was one HIV-infected infant in the entire catchment area. From 2013 to 2017, there were 10 HIV-infected infants and two thus far in 2018. Statewide from 2013 to 2017 there were 41 HIV-infected infants. In the past 2 years, the North Florida region had 31% of the total number of HIV-infected infants. Eight of 12 mothers transmitting infection were known to be HIV infected and were prescribed antiretroviral (ARV) therapy with noncompliance documented in all 8. Two were teenagers; four received no prenatal care and insurance problems were reported in 3 as reasons for ARV noncompliance. Mental illness and/or substance abuse was documented in 6. Three were presumed infected during the third trimester—two tested negative in the first trimester, one was retested early in the third trimester and one was tested only at delivery due to lack of prenatal care. Conclusion: Improved access to prenatal case management and access to mental health and substance abuse services are seriously needed in rural areas. Improving pregnancy compliance with ARV therapy is crucial in preventing vertical transmission. The number of perinatal coordinators needs to be significantly increased to support compliance and provides services. HIV testing in the first and third trimesters should become routine and testing of all (but especially high-risk women such as teenagers and those with mental illness or substance abuse) should be strongly considered at the time of delivery. Disclosures: All authors: No reported disclosures.